The preliminary studies on preparation and characterization of bulk nanoporous zinc as a laser target candidate to generate soft x-ray - Ahmad Shahar, Mohd Lutfi; Abdul Rais, Shamsul Amir; Abd. Wahid, Mohamad Halim; Che Idris, Izzul Hasif; Mazalan, Mazlee; Ahmad, Mohd Fairus; Norizan, Mohd Natashah (International Journal of Integrated Engineering, 2012)
Bulk nanoporous metal has become a reliable source to replace liquid as source to generate EUV lithography which have debris problem to tackle. A solid yet low density porous material promised a low melting point and low plasma density. The plasma density of bulk nanoporous Sn and SnO2 profile plays a key role in the generation of 13.5 nm light for an extreme ultraviolet lithography (EUVL) source from laser produced plasma (LPP). The success of this preparation method might solve problems related to EUV lithography, or even soft Xray (XUV) lithography. In this paper, we present the preliminary result of preparing such ideal low density target in form of bulk metal porous.